Convergent Systems vs. Incremental Stability - Rüffer, Björn S.; van de Wouw, Nathan; Mueller, Markus (Systems Control Lett.)
Two similar stability notions are considered; one is the long established notion of convergent systems, the other is the younger notion of incremental stability. Both notions require that any two solutions of a system converge to each other. Yet these stability concepts are different, in the sense that none implies the other, as is shown in this paper using two examples. It is shown under what additional assumptions one property indeed implies the other. Furthermore, this paper contains necessary and sufficient characterizations of both properties in terms of Lyapunov functions.

A Razumikhin approach for the incremental stability of delayed nonlinear systems - Chaillet, Antoine; Yu. Pogromsky, Alexander; Rüffer, Björn S. (Proc. 52nd IEEE Conf. Decis. Control)
This paper provides sufficient conditions for the incremental stability of time-delayed nonlinear systems. It relies on the Razumikhin-Lyapunov approach, which consists in invoking small-gain arguments by treating the delayed state as a feedback perturbation. The results are valid for multiple delays, as well as bounded time-varying delays. We provide conditions under which the limit solution of a time-delayed nonlinear system to a periodic (resp. constant) input is itself periodic and of the same period (resp. constant). As an illustration, a specific focus is given on a class of delayed Lur’e systems.

Optical coherence tomography assessment of vessel wall degradation in thoracic aortic aneurysms - Real, Eusebio; Eguizabal, Alma; Pontón, Alejandro; Díez, Marta Calvo; Val-Bernal, José Fernando; Mayorga, Marta; Revuelta, José M.; López-Higuera, José M.; Conde, Olga M. (J. Biomed. Opt.)

Separable Lyapunov functions for monotone systems - Rantzer, Anders; Rüffer, Björn S.; Dirr, Gunther (Proc. 52nd IEEE Conf. Decis. Control)
Separable Lyapunov functions play vital roles, for example, in stability analysis of large-scale systems. A Lyapunov function is called max-separable if it can be decomposed into a maximum of functions with one-dimensional arguments. Similarly, it is called sum-separable if it is a sum of such functions. In this paper it is shown that for a monotone system on a compact state space, asymptotic stability implies existence of a max-separable Lyapunov function. We also construct two systems on a non-compact state space, for which a max-separable Lyapunov function does not exist. One of them has a sum-separable Lyapunov function. The other does not.

Regularized Preconditioning for Krylov Subspace Equalization of OFDM Systems over Doubly Selective Channels - Tong, Jun; Schreier, Peter J. (IEEE Wireless Comm. Lett.)

Joint space-time interference mitigation for embedded multi-antenna GNSS receivers - Castañeda, Mario; Stein, Manuel; Antreich, Felix; Tasdemir, Emrah; Kurz, Lothar; Noll, Tobias G.; Nossek, Josef A. (ION GNSS+)

Direct identification of breast cancer pathologies using blind separation of label-free localized reflectance measurements - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (Biomed. Opt. Express)
Breast tumors are blindly identified using Principal (PCA) and Independent Component Analysis (ICA) of localized reflectance measurements. No assumption of a particular theoretical model for the reflectance needs to be made, while the resulting features are proven to have discriminative power of breast pathologies. Normal, benign and malignant breast tissue types in lumpectomy specimens were imaged ex vivo and a surgeon-guided calibration of the system is proposed to overcome the limitations of the blind analysis. A simple, fast and linear classifier has been proposed where no training information is required for the diagnosis. A set of 29 breast tissue specimens have been diagnosed with a sensitivity of 96% and specificity of 95% when discriminating benign from malignant pathologies. The proposed hybrid combination PCA-ICA enhanced diagnostic discrimination, providing tumor probability maps, and intermediate PCA parameters reflected tissue optical properties.

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Post-selection free, integrated optical source of non-degenerate, polarization entangled photon pairs - Herrmann, Harald; Yang, Xu; Thomas, Abu; Poppe, Andreas; Sohler, Wolfgang; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Technik - Alpsancar, Suzana (Die Entwicklung der Psyche in der Geschichte der Menschheit. Auf dem Weg zu einem integrativen Ansatz)

Sooner or Later? – Paradoxical Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (European Accounting Review)

Advance Pricing Agreements (APAs) als Instrument zur Vermeidung von Verrechnungspreiskonflikten – eine kritische Betrachtung - Vollert, Pia; Eikel, Carolin; Sureth-Sloane, Caren (Steuer und Wirtschaft)

A New Model of Higher Education in the European Context - The Leuphana Experience. - Gunkel, Marjaana; Schütz, Julia; Seifert, Andreas; Scharlau, Ingrid; Beck, Karin; Heuer, Claudia (INTED2013 Conference Proceedings: 7th International Technology, Education and Development Conference March 4th-6th, 2013 – Valencia, Spain)

Inszenierungen eines Affekts. Scham und ihre Konstruktion in der Literatur der Moderne. - Heidgen, Michael

To err is human (-like): Effects of robot gesture on perceived anthropomorphism and likeability - Salem, Maha; Eyssel, Friederike Anne; Rohlfing, Katharina; Kopp, Stefan; Joublin, Frank (International Journal of Social Robotics)

Dokumentation der Studie ProLEG: Professionalisierung von Lehrkräften für einen reflektierten Umgang mit Ethnizität und Geschlecht in der Grundschule. Kurz-Dokumentation ausgewählter Daten und Ergebnisse (PLAZ-Forum (Lehrerausbildung und Schule in der Diskussion))

Potential und Herausforderung von Kompetenzforschung auf der Grundlage von IRT-Modellen. - Seifert, Andreas (Kompetenzmessung und -modellierung in den Fachdidaktiken)

Der Hof. Ein Ort kulturellen Handelns von Frauen in der Frühen Neuzeit

Von Opernszenen zum Sprech-Theater: Die Gretchentragödie in Schauspielmusiken zu „Faust“ im 19. Jahrhundert - Tumat, Antje (Vorausdeutungen und Rückblicke. Goethe und Goethe-Rezeption zwischen Klassik und Moderne)

Language lateralization represented by spatiotemporal mapping of magnetoencephalography. - Tanaka, N; Liu, H; Reinsberger, Claus; Madsen, JR; Bourgeois, BF; Dworetzky, BA; Hämäläinen, MS; Stufflebeam, SM (AJNR Am J Neuroradiol)

A millimeter wave quad-phase ring oscillator using 0.13 µm SiGe BiCMOS HBT technology - Ali, U.; Thiede, Andreas (2013 International Semiconductor Conference Dresden - Grenoble (ISCDG))

Zeolitic imidazolate framework-71 nanocrystals and a novel SOD-type polymorph: solution mediated phase transformations, phase selection via coordination modulation and a density functional theory derived energy landscape - Schweinefuß, Maria E.; Springer, Sergej; Baburin, Igor A.; Hikov, Todor; Huber, Klaus; Leoni, Stefano; Wiebcke, Michael (Dalton Transactions)
Keywords: Inorganic Chemistry

Kinetic and Structural Features of a Dyestuff Coaggregation Studied by Time-Resolved Static Light Scattering - Michels, Rolf; Hertle, Yvonne; Hellweg, Thomas; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Co-Aggregation of Two Anionic Azo Dyestuffs at a Well-Defined Stoichiometry - Michels, Rolf; Sinemus, Thomas; Hoffmann, Jan; Brutschy, Bernhard; Huber, Klaus (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Morphology of Blends with Cross-Linked PMMA Microgels and Linear PMMA Chains - Schneider, M.; Michels, R.; Pipich, V.; Goerigk, G.; Sauer, V.; Heim, H.-P.; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

SAXS and ASAXS on Dilute Sodium Polyacrylate Chains Decorated with Lead Ions - Lages, Sebastian; Goerigk, Günter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Einsatzmöglichkeiten und Anwendungsgrenzen der digitalen Bildkorrelation zur Frühdetektion struktureller und funktioneller Schädigungen und Versagensvorhersage in metallischen Werkstoffen, Werkstoffverbunden und Verbundwerkstoffen - Gorny, Bernhard

Running performance analysis in basketball using recorded trajectory data - Jakobsmeyer, Rasmus; Schnittker, Reinhard; Zorn, Rene; Rückert, Ulrich; Baumeister, Jochen (Performance Analysis of Sport IX)

Triggered Indistinguishable Single Photons with Narrow Line Widths from Site-Controlled Quantum Dots - Jöns, Klaus D.; Atkinson, P.; Müller, M.; Heldmaier, M.; Ulrich, S. M.; Schmidt, O. G.; Michler, P.

Qualitätsmanagement in der zivilen Gefahrenabwehr : Optimierung von Führungsprozessen durch interaktive SOPs - Becker, Tobias

Phenomenological Process Simulation and Multiscale Tool Simulation Directed to a Hybrid Forming Process - Sauerland, Kim-Henning

Ursula Kramer: Schauspielmusik am Hoftheater in Darmstadt 1810–1918. Spiel-Arten einer selbstverständlichen Theaterpraxis (= Beiträge zur mittelrheinischen Musikgeschichte 41) - Tumat, Antje (Die Musikforschung)

Ein Fahrerassistenzsystem zur prädiktiven Planung energie- und zeitoptimaler Geschwindigkeitsprofile mittels Mehrzieloptimierung - Gausemeier, Sandra Fabia

Qualifizierung der Direktverschraubung in Fließlochdurchzüge für Aluminiumleichtbaustrukturen des Automobils - Burs, Christian

Approximation, Proof Systems, and Correlations in a Quantum World - Gharibian, Sevag
This thesis studies three topics in quantum computation and information: The approximability of quantum problems, quantum proof systems, and non-classical correlations in quantum systems. In the first area, we demonstrate a polynomial-time (classical) approximation algorithm for dense instances of the canonical QMA-complete quantum constraint satisfaction problem, the local Hamiltonian problem. In the opposite direction, we next introduce a quantum generalization of the polynomial-time hierarchy, and define problems which we prove are not only complete for the second level of this hierarchy, but are in fact hard to approximate. In the second area, we study variants of the interesting and stubbornly open question of whether a quantum proof system with multiple unentangled quantum provers is equal in expressive power to a proof system with a single quantum prover. Our results concern classes such as BellQMA(poly), and include a novel proof of perfect parallel repetition for SepQMA(m) based on cone programming duality. In the third area, we study non-classical quantum correlations beyond entanglement, often dubbed "non-classicality". Among our results are two novel schemes for quantifying non-classicality: The first proposes the new paradigm of exploiting local unitary operations to study non-classical correlations, and the second introduces a protocol through which non-classical correlations in a starting system can be "activated" into distillable entanglement with an ancilla system. An introduction to all required linear algebra and quantum mechanics is included.

QMA variants with polynomially many provers - Gharibian, Sevag; Sikora, Jamie; Upadhyay, Sarvagya (Quantum Information & Computation)
We study three variants of multi-prover quantum Merlin-Arthur proof systems. We first show that the class of problems that can be efficiently verified using polynomially many quantum proofs, each of logarithmic-size, is exactly MQA (also known as QCMA), the class of problems which can be efficiently verified via a classical proof and a quantum verifier. We then study the class BellQMA(poly), characterized by a verifier who first applies unentangled, nonadaptive measurements to each of the polynomially many proofs, followed by an arbitrary but efficient quantum verification circuit on the resulting measurement outcomes. We show that if the number of outcomes per nonadaptive measurement is a polynomially-bounded function, then the expressive power of the proof system is exactly QMA. Finally, we study a class equivalent to QMA(m), denoted SepQMA(m), where the verifier's measurement operator corresponding to outcome "accept" is a fully separable operator across the m quantum proofs. Using cone programming duality, we give an alternate proof of a result of Harrow and Montanaro [FOCS, pp. 633--642 (2010)] that shows a perfect parallel repetition theorem for SepQMA(m) for any m.

In-situ Strukturcharakterisierung von CNT in polymerbasierten Nanokompositen Methodenentwicklung und Anwendung - Gerkens, Stefan

Privacy and Security in Europe. The Privacy & Security-Research Paper Series, edited by Emilio Mordini and Christian Fuchs. Research Paper Number 6 - Fuchs, Christian

Grundlegende Untersuchung der Prozess- und Werkzeugparameter und ihrer Wechselwirkungen für das thermo-mechanisch unterstützte inkrementelle Umformverfahren des Reib-Drückens - Hornjak, Daniel

Theorising and Analysing Digital Labour: From Global Value Chains to Modes of Production - Fuchs, Christian (The Political Economy of Communication)

Political Economy and Surveillance Theory - Fuchs, Christian (Critical Sociology)

The Diamond Model of Open Access Publishing: Why Policy Makers, Scholars, Universities, Libraries, Labour Unions and the Publishing World Need to Take Non-Commercial, Non-Profit Open Access Serious - Fuchs, Christian; Sandoval, Marisol (tripleC: Communication, Capitalism & Critique)

What Is Digital Labour? What Is Digital Work? What’s Their Difference? And Why Do These Questions Matter for Understanding Social Media? - Fuchs, Christian; Sevignani, Sebastian (tripleC)

Capitalism or Information Society? The Fundamental Question of the Present Structure of Society - Fuchs, Christian (European Journal of Social Theory)

Societal and Ideological Impacts of Deep Packet Inspection (DPI) Internet Surveillance - Fuchs, Christian (Information, Communication and Society)

Class and Exploitation on the Internet - Fuchs, Christian (Digital Labor. The Internet as Playground and Factory)

„Reißverschluß in 600m“ – Über textile Wahrnehmungsmuster - Kraft, Kerstin